ANALYSIS OF TILAPIA AGRIBUSINESS SYSTEM IN CALM WATER POUNDS IN KEPAHIANG DISTRICT, BENGKULU PROVINCE - Dewi, Neti Sutra; Irnad; Reflis (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The purpose of this study was to analyze the production process, marketing and the role of supporting institutions for tilapia development. This research was conducted in Kepahiang and Ujan Mas subdistict, Districts of Kepahyang, Bengkulu Province in which 76 tilapia producers were selected ramdomlay and interviewed. Analysis of data involved income and R/C ratio, marketing margins as well as a descriptive qualitative analysis. The results showed that the production income of tilapia was IDR2,129,587, - and an R/C ratio of 1.29. This resealsoh found that there are three marketing channels including (i) farmer to consumer, (ii) farmer to diluent to consumer, and (iii) farmer to collector trader to diluent to consumer. The marketing channel for Tilapia in Kepahiang Regency is efficient and the third channel is the main channel for marketing Tilapia. The role of supporting institutions involve (i) government provides feed to farmers and machine assistance to farmer groups, (ii) extension workers are tasked with improving the human resources of tilapia farmers, and (iii) banking support credit farmers according to the terms and conditions that apply